Women’s Submissiveness in Bapsi Sidhwa’s The Pakistani Brid - et. al., Gunia Beniwal (International Journal of Modern Agriculture, 2021)
Postcolonial literature approaches to expose the colonial philosophy by feminine gender, social exclusion and degraded punishments as the ‘other’. The author of the novel emphasis on the difficulties of deformed identities of fictitious characters, dislocation, gender biasness, subjugation and the predicaments of the citizens existing in colonized societies. This research paper concentrates on the predicaments of the colonized women, their dislocation, and isolation due to acts of cultural conflict and dominance of politics. The novel The Pakistani Bride is drawn upon the basis of an original event which displays story of a girl named Zaitoon and to emphasis on Bapsi Sidhwa where she initiates a harsh attack of patriarchal society on Women. In the colonial times, women were treated as a subject of lust and with no social status. To begin with, it is a story of Zaitoon’s life struggle for survival and also men live under a burden of honour protection to dismay women. Bapsi Sidhwa gives a picture of gut wrenching incidents of inhuman barbarity, unclothed women howling for relief, and endorses the unfair treatment within the house against women. This gut wrenching incidents does represent the most barbaric action in the theological and cultural aftermath in the novel The Pakistani Bride.